Implementing a peer recovery coach model to reach low-income, minority individuals not engaged in substance use treatment. Issue 4 (2nd October 2021) - Kleinman, Mary B.; Doran, Kelly; Felton, Julia W.; Satinsky, Emily N.; Dean, Dwayne; Bradley, Valerie; Magidson, Jessica F.
Abstract: Background: Low-income, racial/ethnic minority individuals face significant barriers in access to substance use (SU) treatment. Peer recovery coaches (PRCs), individuals with lived experience with substance use disorder (SUD), may be uniquely well suited to assist those encountering barriers to treatment. PRCs can also help reach those not engaged in treatment to promote harm reduction and support linkage-to-care when embedded in community rather than clinical settings. This study evaluated a community-based program in which a PRC facilitated linkage to and supported retention in SU treatment. Methods: Guided by the RE-AIM framework, we evaluated implementation of the intervention in a community resource center (CRC) serving homeless and low-income residents of Baltimore City. We examined the reach, effectiveness, adoption, and implementation of this PRC model. Results: Of 199 clients approached by or referred to the PRC, 39 were interested in addressing their SU. Of those interested in addressing SU, the PRC linked 64.1% ( n  = 25) to treatment and was able to follow up with 59.0% ( n  = 23) at prespecified time points after linkage (24–48 hours, 2 weeks, and 1 month). Fifty-two percent ( n  = 13) of clients linked to SU treatment remained in treatment at 30 days post-linkage. Of clients who did not remain in treatment, 77% ( n  = 10) continued contact with the PRC. Conclusions: Results indicate the utility of the CRC's approach in linking people to treatment for SU and addressing barriers to care through work with a PRC. Findings also highlight important barriers and facilitators to implementation of this model, including the need for adaptation based on individual goals and fluctuations in readiness for treatment.